Profiting logistics businesses through optimised light rail transit system: Application to the city of Bangkok. Issue 1 (1st January 2021) - Apichottanakul, Arthit; Thanawaritwatthana, Nanpipat; Arunyanart, Sirawadee
Abstract: The objective of this study was to develop a new method for freight movement in urban areas by combining a light rail transit system and a road transport system to distribute and deliver parcels. Utilisation of light rail transportation systems for parcel delivery can help reduce traffic congestion and air pollution in cities. This paper presents a location–allocation model to determine the optimum number and location of light rail stations suitable to establish rail distribution hubs, in a bid to minimise transportation costs. A case study is conducted to assess this approach in the city of Bangkok. The results show that the cost, time, and distance of transportation can be reduced by 10%, 16.67%, and 33.33%, respectively.